Analysis Of Revenue And Added Value Of Aroma Jaya Salted Fish Processing Business - Risma Dwi Putri; Slamet Abadi; Bayu Budiandrian (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2024)
Fish processing is an alternative for dealing with abundant catches that cannot be remarketed due to a decrease in quality. Processing of fishery products in the marine fisheries subsector, especially fish commodities, has quite a large market potential and can create promising business opportunities. This research aims to analyze how much income is obtained from the Aroma Jaya salted fish processing business and to analyze the added value of 5 types of salted fish in the Aroma Jaya salted fish processing business in Blanakan Village, Blanakan District, Subang Regency. The data collection technique used in this research is key informant, and the data obtained will be verified by the informant. This research uses primary data and secondary data. The data analysis method used is a quantitative descriptive method with a case study approach. Quantitative descriptive analysis is used to analyze businesses which includes analysis of costs, revenues, income and added value (added value) products of the Aroma Jaya salted fish processing business. The results of the analysis show that the total costs used for processing 5 types of salted fish are IDR 671,278,750.00 per month. The average receipt of 5 types of salted fish is IDR 759,958,500.00 per month. The average income for 5 types of salted fish is IDR 88,679,750.00 per month. The added value obtained in one month for 5 types of salted fish is IDR 34,936.81.00 per kg of raw material, with a value-added ratio of around 27.6%/kg. The company's profit from 5 types of salted fish is IDR 19,707.81 per kg, with a profit rate of 56.4%/kg.